ESG in the boardroom: Evidence from the Malaysian market - Kamilah Kamaludin; Izani Ibrahim; Sheela Sundarasen; Ova Faizal (International Journal of Corporate Social Responsibility (JCSR), 2022)
This study examines the influence of boards' characteristics with respect to independence, diversity, and diligence on the environment, social, governance (ESG) disclosure among Bursa Malaysia companies. The board characteristics are proxied by the percentage of independent directors, women on the board, and the number of board meetings, respectively. We collected data from all 785 companies listed on the Kuala Lumpur Stock Exchange. Our final sample consisted of 91 companies that have an ESG disclosure score. Using GLS panel regression analysis, our findings overall indicate that board independence and diversity enhance ESG disclosure practice significantly for companies in all sectors. However, board diligence is related negatively to ESG disclosure. As expected, the significance of the relations among the board characteristics and the ESG disclosures are more profound from 2014 onward, largely because of changes in regulatory requirements. Our study provides new understanding and insights pertaining to the importance of board independence and board diversity on ESG initiatives and disclosures in the Malaysian context. This research complements studies in the areas of sustainability and strategy, and contributes to business practices with respect to the composition of boards of directors.
Keywords: 650; Board diligence; Board independence; ESG disclosure; Malaysia; Women on the board